Establishing the wave climate influence on the morphodynamics of a coastal lagoon inlet - Plecha, S.
The morphologic changes in estuaries and coastal lagoons are very complex and constitute a challenging task in coastal research. The bathymetric changes result from the combined action of tides, waves, rivers discharge and wind stress in the area of interest. Additionally, an accurate knowledge of the sediment transport is essential to achieve a good morphological characterization. This work establishes the influence of the wave climate on the morphodynamics of the Ria de Aveiro lagoon inlet by analysing the numerical results of the morphodynamic modelling system MORSYS2D. The numerical simulations considered a realistic coupled forcing of tidal currents and waves. The computed sediment fluxes and bathymetric changes are analysed and compared with the erosion and accretion trends obtained from the numerical simulations forced only by tidal currents, in order to establish the wave climate influence. The final bathymetry and the corresponding changes are compared with bathymetric data collected through surveys. It is concluded that: (a) the morphodynamics of the study area is dominated by the wave regime in the lagoon inlet and nearshore areas, while in the inner areas is tidally dominated; and (b) the inclusion of the wave regime forcing constitutes an improvement in order to accurately reproduce the local morphodynamics.